Aqueous phase synthesis of all-inorganic halide perovskite CsPbClxBr3-x nanocrystals using CsTFA as cesium source and surface ligand - Qile Li; Ke Xu; Shuochen Fan; Haipeng Zhang; Xianqi Wei; Chao Xu; Xiaodong Luan; Zhongxia Wang; Huaping Peng; Linxin Shi (Next Materials, 2025)
All-inorganic halide perovskite CsPbX3 (X=Cl, Br, I) nanocrystals (NCs) have become attractive optoelectronic materials due to their excellent optical and electronic properties. However, the ionic properties and surface defects of halide perovskite make them highly susceptible to decomposition and degradation in water, which significantly hinders the stability and luminescence performance of CsPbX3 NCs. Therefore, synthesizing high-stability perovskite nanocrystals in the aqueous phase is a crucial challenge. Here, we have developed a method for the synthesis of CsPbClxBr3-x NCs with high stability via in-situ crystallization in aqueous phase using cesium trifluoroacetate (CsTFA) as cesium source and surface ligand. CsTFA not only provides Cs+ for the perovskite lattice but also possesses its own TFA- as a strong surface ligand, which, in cooperation with 4-bromobutyric acid (BBA) and oleylamine (OLA) surface ligands, will facilitate the formation of more regular nanocrystals and substantially reduce the defects on the crystal surface. The CsPbClxBr3-x NCs obtained in an aqueous solution exhibit a cubic crystal structure with photoluminescence quantum yields > 90 %. After being dispersed in an aqueous solution for 90 h, the wavelength and full width at half-maximum of the PL of CsPbClxBr3-x NCs have no significant change, and the PL intensity can maintain 90.3 % of their initial one, indicating that the structure of CsPbClxBr3-x NCs is unchanged. Moreover, the CsPbClxBr3-x NCs sample maintained high stability and good luminescence properties even after dilution with water tens of times. The results provide a viable design strategy for synthesizing cesium-based perovskite nanocrystals with high stability using CsTFA in an aqueous phase or other medium.